The Isolation of Zizanoic Acid Isolated from Vetiveria Zizanioides Harvesterd in Vietnam and its Transformation to the Ester Derivatives - Nguyen, Tran Thi Thao; Thu, Bui Thai Thanh; Hung, Mac Dinh (VNU Journal of Science: Natural Sciences and Technology, 2025)
Vetiver, known as Vetiveria zizanioides or Chrysopogon zizanioides , is cultivated in various parts of the world, with major cultivation areas in Nghe An and Thai Binh provinces of Vietnam. It is highly valued for its pharmacological and economic properties, particularly in the fragrance industry. This study aimed to isolate zizanoic acid through an acid-base extraction from Vetiver roots grown and harvesterd in Quang Nam, Vietnam, and subsequently convert it into ester derivatives using the Fischer esterification process. The results showed moderate to excellent yields, giving methyl zizanoate, ethyl zizanoate, and butyl zizanoate.